Design of open-source joint C and VHDL "twin" program module libraries for digital signal processing - Tao Zeng; Shilong Xue; Auger, F. (2009 International Conference on Measuring Technology and Mechatronics Automation, 2009)
In the domain of digital signal processing, the microcontrollers, the Digital Signal Processors(DSPs) and the Field Programmable Gate Arrays(FPGAs) are widely used.The microcontrollers and DSPs can use the C language, whilethe FPGAs use the VHDL language. To ease the coding, simulation and implication of digital signal processing, a new engineering tool is presented. The open-source joint C and VHDL "twin" program module libraries have many advantages. Firstly, they make choosing the ideal chip amongthe microcontrollers, DSPs and FPGAs more easily. Secondly, they can solve the problem of simulation and fixing the length of signals in VHDL language. Thirdly, they make the job of constructing programs more efficient.